(untitled) (Journal of actual problems of jurisprudence, 2022)
This article is devoted to one of the urgent problems of modern customs law. The aspects of customs inspection considered in the article, as one of the forms of customs control, have a double meaning. On the one hand, the customs inspection helps the customs authorities to identify violations of customs and tax legislation committed by participants in foreign economic activity. On the other hand, customs inspections (especially if they are carried out frequently) prevent participants in foreign economic activity from freely carrying out business activities. Therefore, in the practical activities of customs authorities there, when organizing and conducting customs control, it is important to carry out actions clearly regulated by customs legislation. Since not only the detection of violations of customs legislation, but also the minimization of complaints and appeals to judicial authorities from participants in foreign economic activity regarding illegal actions of customs officials during customs inspection will directly depend on the exact implementation of the norms of customs legislation regulating the procedure for customs inspection. Identification of all problems related to the organization and conduct of customs inspections of participants in foreign economic activity will help make this necessary form of customs control transparent and effective. All these issues are considered by the author in the article below. The conclusions made by the author are based on a comprehensive study of the norms of customs legislation regulating the organization and conduct of various types of customs inspection, as well as materials of practical activities of customs authorities and judicial practice on customs inspection. The practical significance of this article lies in the possibility of using theoretical results when conducting further research in the field of customs law, in general, and customs control, in particular. Also, the results of the article can be used in the development and improvement of the norms of the customs legislation of the Republic of Kazakhstan. Keywords: customs control, customs legislation, customs inspection, desk customs inspection, exit customs inspection.